Tax policy reform and universal basic income effectiveness in a currency union: Implications for long-term growth, inequality, and welfare - Thierry U. Kame Babilla (Journal of Government and Economics (JGE), 2023)
This paper aims to assess tax policy reforms that can sustain universal basic income programs and foster long-term growth and welfare in a currency union that faces fiscal rule constraints and inequality. To address this ongoing government and economics' debate, we developed a Dynamic Stochastic General Equilibrium Model of universal basic income enriched with three fiscal policy strategies. Results demonstrate that the effectiveness of universal basic income on long-term growth, inequality, and welfare depends on the type of fiscal policy adopted by government to fund it, notably the trade-off between increasing the tax base or reducing public spending. First, under normal circumstances, universal basic income funded by completely eliminating oil subsidies appears to be the best policy for reducing inequality while increasing growth and welfare. Second, when the currency union faces a crisis, a universal basic income funded by increases in different taxes is more effective in combating stagflation and inequality than a universal basic income funded by total oil subsidy elimination. The welfare analysis confirms that, universal basic income funded by the increase in tax on capital gains and the increase in tax on corporate income is successful in reducing income inequality and consumption inequality and improving households' living standards, its effects lead to higher welfare gains when the economy faces a crisis rather than the economy in normal times.
Keywords: D63; E12; E62; E63; E64; H21; H25; H53; I38; O47; 330; Currency union; DSGE model; Inequality; Long-term growth; Tax policy reforms; Universal basic income; Welfare